(untitled) (Bangladesh Journal of Livestock Research, 2020)
This study was conducted to know the production performance of laying hen by using different graded level of linseed. At 56 weeks of age, a total of 160 laying hens were raised up to 63 weeks of age. All hens were fed a basal corn soyabean meal diet. The experiment was allowed 4 dietary treatments (T0, no addition of whole linseed in the basal diet; T1, addition of 5% whole linseed; T2, addition of 10% whole linseed and T3, addition of 15% whole linseed) with 5 replications and per replication contains eight hens. Egg production, feed intake, egg weight of each treatment was recorded. Egg samples were collected and analyzed for egg quality. The results showed that egg production and egg mass (kg) exhibited for all dietary treatment groups were unaffected (P>0.05) by feeding linseed to the laying hens. Feed Conversion Ratio (FCR) was found significant difference within the four dietary group (P<0.05). Egg quality aspects such as yolk weight, egg weight, HU and yolk index were not differed significantly (P>0.05) among treatments. A trend for lower yolk weight was observed in birds fed 10% linseed, where as the highest yolk weight percentage was recorded in control diet. There was no statistical difference among the different diets for yolk index. The results of the present trial suggested that feeding linseed to the laying hens has no detrimental effects on egg production and egg quality. Bangladesh J. of Livestock Res. 20(1-2): 48-53, Jan-Dec 2013